Method for making low variation coefficient 2 # line P.O 42.5 cement - ZHANG FANG; CHEN LIUJUN; LIAO DING; HU ZHONGWEN; TAN JINYING; LU YANLING; LONG SHENGKANG; DENG YULIAN; YANG MAOXIN; CHEN LIUFENG; ZHANG GUOXIA; LIU LIJUN; et al. (2015)
The invention discloses a method for making low variation coefficient 2 # line P.O 42.5 cement, and the method is as follows: mixing limestone, pulverized coal ash and granulated blast furnace slag powder in the following portions of 6 parts of limestone: 6.2 parts of pulverized coal ash: 5.6 parts of granulated blast furnace slag powder, adding the limestone, pulverized coal ash and granulated blast furnace slag powder into a cement mill for production of the 2 # line P.O 42.5 cement by vertical mill grinding technology. The method for making the low variation coefficient 2 # line P.O 42.5 cement can overcome the defects of complex components, unreasonable proportion and poor stability, and the like in the prior art, and has the advantages of realization of simple composition, reasonable ratio and good stability.